2013
DOI: 10.1016/j.jvs.2012.07.051
|View full text |Cite
|
Sign up to set email alerts
|

Exercise capacity is the strongest predictor of mortality in patients with peripheral arterial disease

Abstract: Objective The objective of this study was to assess the predictive value of clinical and exercise test variables in patients with peripheral arterial disease (PAD). Methods 725 PAD patients referred for exercise testing at the Palo Alto Veterans Hospital between 1997 and 2011 were subjected to a customized symptom-limited ramp treadmill protocol. Detailed clinical and exercise test data were collected at baseline and patients were followed for a mean of 11.3±6.3 years. Results During follow up, there were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
92
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 19 publications
1
92
1
1
Order By: Relevance
“…30,31 Non-invasive limb pressure measurements were not assessed by these analyses. The prognostic value of combined exercise capacity and distal non-invasive pressure measurements on mortality is a tempting target for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Non-invasive limb pressure measurements were not assessed by these analyses. The prognostic value of combined exercise capacity and distal non-invasive pressure measurements on mortality is a tempting target for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, before an elective operation for AAA, a lower exercise capacity, which is presumably associated with less physical activity, was associated with higher mortality (12). These same associations have been observed in patients with CAD and PAD (18,21).…”
Section: Discussionmentioning
confidence: 60%
“…Consequently, the more rapid occurrence of exercise-limiting, maximal claudication pain not only resulted in a shorter PWT, but it indicates that the lower MMSE group is not capable of sustaining ambulation at an intensity of approximately 4 metabolic equivalents (MET’s). The shorter PWT of the lower MMSE group is clinically relevant given that exercise capacity of patients with PAD, as measured by MET’s calculated from the duration of walking on a graded treadmill test, is the strongest predictor of mortality 35 . Furthermore, we have previously found that sedentary symptomatic patients with PAD who do not perform ambulatory activity above light intensities have a higher rate of mortality 36 .…”
Section: Discussionmentioning
confidence: 99%